GPCRs in the regulation of the functional activity of multipotent mesenchymal stromal cells - Chechekhin, Vadim I.; Kulebyakin, Konstantin Yu.; Kokaev, Romesh I.; Tyurin-Kuzmin, Pyotr A. (Frontiers in Cell and Developmental Biology, 2022)
Adipose tissue is one of the tissues in the human body that is renewed during the whole life. Dysregulation of this process leads to conditions such as obesity, metabolic syndrome, and type 2 diabetes. The key role in maintaining the healthy state of adipose tissue is played by a specific group of postnatal stem cells called multipotent mesenchymal stromal cells (MSCs). They are both precursors for new adipocytes and key paracrine regulators of adipose tissue homeostasis. The activity of MSCs is tightly adjusted to the needs of the organism. To ensure such coordination, MSCs are put under strict regulation which is realized through a wide variety of signaling mechanisms. They control aspects of MSC activity such as proliferation, differentiation, and production of signal molecules via alteration of MSC sensitivity to hormonal stimuli. In this regard, MSCs use all the main mechanisms of hormonal sensitivity regulation observed in differentiated cells, but at the same time, several unique regulatory mechanisms have been found in MSCs. In the presented review, we will cover these unique mechanisms as well as specifics of common mechanisms of regulation of hormonal sensitivity in stem cells.